Air quality and health effects of biogenic volatile organic compounds emissions from urban green spaces and the mitigation strategies - Ren, Yuan; Qu, Zelong; Du, Yuanyuan; Xu, Ronghua; Ma, Danping; Yang, Guofu; Shi, Yan; Fan, Xing; Tani, Akira; Guo, Peipei; Ge, Ying; Chang, Jie (Environmental pollution (1987), 2017)
Biogenic volatile organic compounds (BVOCs) emissions lead to fine particulate matter (PM2.5) and ground-level ozone pollution, and are harmful to human health, especially in urban areas. However, most BVOCs estimations ignored the emissions from urban green spaces, causing inaccuracies in the understanding of regional BVOCs emissions and their environmental and health effects. In this study, we used the latest local vegetation datasets from our field survey and applied an estimation model to analyze the spatial-temporal patterns, air quality impacts, health damage and mitigating strategies of BVOCs emissions in the Greater Beijing Area. Results showed that: (1) the urban core was the hotspot of regional BVOCs emissions for the highest region-based emission intensity (3.0 g C m−2 yr−1) among the 11 sub-regions; (2) urban green spaces played much more important roles (account for 62% of total health damage) than rural forests in threating human health; (3) BVOCs emissions from green spaces will more than triple by 2050 due to urban area expansion, tree growth and environmental changes; and (4) adopting proactive management (e.g. adjusting tree species composition) can reduce 61% of the BVOCs emissions and 50% of the health damage related to BVOCs emissions by 2050. [Display omitted] •Urban core is the hotspot of biogenic volatile organic compounds (BVOCs) emissions in the Greater Beijing Area.•Neglecting BVOCs emissions from urban green spaces leads to a 62% underestimation of the related health damage.•BVOCs contribute significantly to ozone pollution while make limited contribution to PM2.5 pollution.•BVOCs emissions from urban green spaces will triple by 2050, and 61% of these emissions can be reduced through management. Although BVOCs emissions from urban green spaces make limited contribution to regional emissions, their health impacts could be significant in urban areas.